New forms of memory institutionalisation in Balkans and Poland (comparative study of three cases) - Bogusławska, Magdalena (Balcanica Posnaniensia. Acta et studia, 2018)
The subject of the article is the characteristics of modern forms of memory institutionalization – the kind of commemorative practices and the related production and dissemination of knowledge in the public space. This topic seems especially important but also controversial in post-socialist countries, in which a major process of revision of the past is continues. This process becomes a part of the political pluralization of the public sphere and the expression of the emancipation of various previously marginalized groups. Using the example of the three museum: Museum of the Macedonian Struggle for Sovereignty and Independence, War Childhood Museum in Sarajevo and „Polin” Museum of the History of Polish Jews, the author discusses: – the articulation and afirmation of subjectivity by means of museum as an institution – the mechanism for shaping the authority of institutions so as to legimitize the interpretation of the past – the relationship between the particular, often fragmented registers of the memory and the dominant power discourses.